Clinical Pharmacy 2015
DOI: 10.1136/ejhpharm-2015-000639.25
|View full text |Cite
|
Sign up to set email alerts
|

CP-025 Patients’ adherence-related beliefs about medicines prescribed for long-term conditions in hiv patients

Abstract: BackgroundThere has been an increase in the number of chronic conditions concomitantly present in HIV-infected individuals and correspondingly, in comedication. Beliefs play a crucial role in medicines adherence.PurposeTo investigate the relationship between beliefs (necessity and concerns) of HIV-infected patients about comedication and their adherence.Material and methodsWe conducted a cross-sectional study between May–July 2014, that included HIV-infected patients treated with antiretroviral treatment (ART)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In our study, the overall adherence calculated was high for ART, but particularly low for concomitant medication, where the main polypharmacy pattern was precisely cardiovascular. This suggests prioritization of drug intake by patients based on their beliefs and perceptions about drugs 34 . The results of the Borrego et al 35 study showed that adherence problems begin at the time of prescription, because one third of patients will not even collect the prescribed medication.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the overall adherence calculated was high for ART, but particularly low for concomitant medication, where the main polypharmacy pattern was precisely cardiovascular. This suggests prioritization of drug intake by patients based on their beliefs and perceptions about drugs 34 . The results of the Borrego et al 35 study showed that adherence problems begin at the time of prescription, because one third of patients will not even collect the prescribed medication.…”
Section: Discussionmentioning
confidence: 99%